2011
DOI: 10.1016/j.pscychresns.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Rostral anterior cingulate cortex activity and early symptom improvement during treatment for major depressive disorder

Abstract: In treatment trials for Major Depressive Disorder (MDD), early symptom improvement is predictive of eventual clinical response. Clinical response may also be predicted by elevated pretreatment theta (4-7 Hz) current density in the rostral anterior cingulate (rACC) and medial orbitofrontal cortex (mOFC). We investigated the relationship between pretreatment EEG and early improvement in predicting clinical outcome in 72 MDD subjects across three placebo-controlled treatment trials. Subjects were randomized to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 53 publications
4
38
0
Order By: Relevance
“…The neurobiological basis of the placebo response is characterized by an increase in the metabolic activity of the frontal and striatal cortical regions [20] and increased endogenous opioid release in the subgenual anterior cingulate cortex, nucleus accumbens, midline thalamus, and amygdala [21,22]. The placebo response has also been linked to increased baseline resting state functional connectivity of the rostral anterior cingulate cortex (rACC) within the salience network [23] and to increased pretreatment rACC activity in 2 EEG studies [24,25]. Previous studies of neuroimaging biomarkers of placebo response have been limited by small sample sizes and a lack of comparison with other clinical and biobehavioral markers [21,23].…”
Section: Introductionmentioning
confidence: 99%
“…The neurobiological basis of the placebo response is characterized by an increase in the metabolic activity of the frontal and striatal cortical regions [20] and increased endogenous opioid release in the subgenual anterior cingulate cortex, nucleus accumbens, midline thalamus, and amygdala [21,22]. The placebo response has also been linked to increased baseline resting state functional connectivity of the rostral anterior cingulate cortex (rACC) within the salience network [23] and to increased pretreatment rACC activity in 2 EEG studies [24,25]. Previous studies of neuroimaging biomarkers of placebo response have been limited by small sample sizes and a lack of comparison with other clinical and biobehavioral markers [21,23].…”
Section: Introductionmentioning
confidence: 99%
“…Regions involved in these networks have emerged as biological markers of response to antidepressant treatments (8-13). Yet, the ability of these biomarkers to selectively distinguish drug-specific effects from other non-specific elements of the treatment response, such as the placebo effect, is still limited, with very few studies specifically addressing biomarkers of non-specific elements of antidepressant treatment response (14, 15). This is not a small concern, as placebo response rates in antidepressant clinical trials average 31-45% compared with response rates to antidepressants of ~50% and have increased at a rate of 7% per decade over the last 30 years (16, 17).…”
Section: Introductionmentioning
confidence: 99%
“…Other brain areas implicated in the mood and anxiety disorders are: the insula, linked to self-awareness and autonomic regulation of emotions (Craig, 2009;Paulus and Stein, 2006); the hippocampus, involved in memory formation, learning, sensitivity to context, and regulation of stress, as well as a major site of neurogenesis (Bellani et al, 2010;Brooks et al, 2012;den Heijer et al, 2012); the thalamus, a processing centre for sensation and motor regulation, which also plays a role in awareness, attention, memory, and language (Herrero et al, 2002;Matsumoto et al, 2001); the cingulate cortex, involved in the regulation of both cognitive and emotional processing with functions in directed attention and motivated behaviour (Amiez et al, 2012;Blair et al, 2012;Bush et al, 2000;Etkin et al, 2011); and the superior temporal gyrus (STG), implicated not only in auditory processes, but also in language processing, social cognition, and emotion perception in faces (Bigler et al, 2007;Domínguez-Borràs et al, 2009;Turk-Browne et al, 2010). Furthermore, research on the treatment of affective disorders has demonstrated that treatment restores the function of these regions (e.g., Arce et al, 2007;Korb et al, 2011).…”
Section: Introductionmentioning
confidence: 99%